A argyrodite-type solid electrolyte and its preparation method and application

By doping W, O, and Br elements in the solid electrolyte of sulfur silver germanium type, the problems of low ionic conductivity and poor air stability are solved, high ionic conductivity and air stability are achieved, and the electrochemical performance of the battery is improved, meeting the high energy density and long cycle life requirements of all-solid state batteries.

CN119263232BActive Publication Date: 2025-04-29SHANGHAI FIRM LITHIUM NEW ENERGY TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411794222.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-29
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

In practical applications, sulfur-silver germanium ore solid electrolytes face the problems of low ionic conductivity, poor air stability and insufficient mechanical properties, and it is difficult to meet the needs of high ionic conductivity, air stability and electrochemical performance at the same time.

Method used

By doping three elements of W, O and Br on the substrate of Li5.5PS4.5Cl1.5, their chemical structure and disorder are adjusted, thereby improving ionic conductivity and air stability, and optimizing the crystal structure to improve the power density and cycling stability of the battery.

Benefits of technology

The high ionic conductivity (up to 10ms/cm), air stability and electrochemical performance of sulfur-silver germanium ore-type solid electrolytes have been achieved, meeting the needs of all-solid-state batteries in terms of high energy density, safety and long cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263232B_ABST
    Figure CN119263232B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of solid electrolytes, and relates to a thiogermanate solid electrolyte, a preparation method thereof, and an application. The molecular formula is Li 5.5‑x P 1‑x W x S 4.5‑3x O 3x Cl y Br 1.5‑y . During the preparation, raw materials are pre-mixed according to a molar ratio and ball-milled to obtain solid electrolyte powder; then the solid electrolyte powder is pressed into an electrolyte sheet and sintered to obtain the thiogermanate solid electrolyte. The multifunctional electrolyte of the present invention has good stability in air while improving the ionic conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of solid electrolytes, and specifically relates to an argyrodite-type solid electrolyte and a preparation method and application thereof, and in particular to a controllable construction of a multifunctional solid electrolyte and its application in an all-solid-state battery. Background Art

[0002] With the widespread use of electric vehicles and portable electronic devices, the demand for high energy density and superior safety battery technology is increasing. Solid electrolytes, as a key component, have attracted widespread attention because they can replace traditional liquid electrolytes. Solid electrolytes have the advantages of preventing electrolyte leakage, improving battery safety, and enhancing cycle life, providing important support for the development of next-generation battery technology.

[0003] Traditional liquid electrolytes (such as organic solvents and salts) are volatile and flammable at high temperatures, and have problems such as battery capacity attenuation and poor safety, which limit the further development of batteries in terms of high performance and high safety. Solid electrolytes are considered to be an effective way to overcome these problems due to their low leakage, high chemical stability, and wide operating temperature range.

[0004] Argentite-type solid electrolytes have their unique advantages, such as: 1) Excellent ionic conductivity: Argentite structure provides a stable ion transmission path, which helps to improve the conductivity and charge and discharge efficiency of the battery. 2) Strong chemical stability: Under high temperature and high voltage conditions, argyrodite-type electrolytes show good chemical stability, reducing the risk of electrolyte decomposition and battery attenuation. 3) Excellent interface compatibility: Argentite-type electrolytes can effectively form a good interface with electrode materials, reduce interface resistance, and improve the cycle stability and energy efficiency of the battery. At present, argyrodite-type solid electrolytes are increasingly attracting widespread attention from researchers.

[0005] Although argyrodite-type solid electrolytes have the above advantages, they still face some challenges in practical applications: 1) Optimization of ionic conductivity. The ionic conductivity of solid electrolytes is usually lower than that of liquid electrolytes, which may lead to a decrease in the energy density and power density of the battery. Improving the ionic conductivity of argyrodite-type electrolytes is a key issue, involving research in many aspects such as material synthesis and structural optimization. 2) Air stability. Sulfide solid electrolytes easily react with water in the air to produce hydrogen sulfide gas. 3) Mechanical properties. Solid electrolyte materials usually need to have certain mechanical strength and flexibility to adapt to pressure changes and mechanical stress during battery assembly. The performance of argyrodite-type electrolytes in this regard needs to be further improved to meet the needs of practical applications.

[0006] At present, in order to solve the above problems, relevant reports have been made, and the published patents mainly include CN114883642A, CN114744287A, CN114914527A, CN114649562A, and CN114899480A. The main method is to adopt doping modification. However, it is still a great challenge to achieve high ionic conductivity and good air stability at the same time. Summary of the invention

[0007] The purpose of the present invention is to provide a argyrodite-type solid electrolyte and a preparation method and application thereof in view of the problems existing in the prior art.

[0008] Although there have been many reports on the modification of sulfide electrolytes by doping with metal oxides, they still cannot meet the current needs (either low ionic conductivity, poor electrochemical performance, or poor air stability). A system that simultaneously meets high ionic conductivity, high air stability, and stable electrochemical performance has not yet been developed. Multifunctionality is the innovation of the electrolyte developed in this invention. 5.5 PS 4.5 Cl 1.5 By doping the substrate with three elements of W, O and Br, the ion conductivity can be increased to 10 ms / cm. The multifunctional electrolyte of the present invention has good stability to air while increasing the ion conductivity.

[0009] The purpose of the present invention can be achieved by the following scheme:

[0010] On the one hand, the present invention provides a argyrodite-type solid electrolyte, the chemical molecular formula of which is Li 5.5-x P 1- x W x S 4.5-3x O 3x Cl y Br 1.5-y ;

[0011] Among them, the value of x is 0.001<x<0.5, 0.7<y<0.9.

[0012] The molecular formula of the argyrodite-type solid electrolyte is preferably Li 5.5-x P 1-x W x S 4.5-3x O 3x Cl 0.8 Br 0.7 The present invention can improve the disorder of the system (i.e., the entropy increase process) by doping with Br elements, thereby improving its ion conductivity, thereby accelerating the migration of lithium ions, and thus weakening the influence of the interface layer formed between the positive electrode and the electrolyte.

[0013] The introduction of oxygen in the present invention can not only improve air stability, but also help form a stable interface layer, reduce the interface resistance between the solid electrolyte and the electrode, and improve the performance and cycle stability of the battery. The electrochemical reaction kinetics in the battery helps to regulate the charge and discharge rate and cycle life of the battery.

[0014] The introduction of tungsten in the present invention not only widens the ion channel and improves the ion conductivity, but also helps to optimize the crystal structure of the sulfide solid electrolyte, improve its ion conductivity, and increase the power density and durability of the battery. Tungsten doping will not destroy the original crystal structure, as can be seen from the measured XRD diagram.

[0015] In addition, sulfide solid electrolytes may precipitate when used at high temperatures or for long periods of time, and the addition of tungsten can effectively inhibit this precipitation phenomenon and maintain the stability of the electrolyte. Of course, tungsten can also change the ion transport path and kinetics in sulfide solid electrolytes, optimizing the battery's charge and discharge performance and cycle stability.

[0016] On the one hand, the present invention provides a method for preparing the argyrodite-type solid electrolyte, comprising the following steps:

[0017] S1. Premixing the raw materials according to the molar ratio and ball milling to obtain solid electrolyte powder;

[0018] S2. Pressing the solid electrolyte powder into sheets to obtain electrolyte sheets, and vacuum sintering to obtain argyrodite-type solid electrolyte.

[0019] As an embodiment of the present invention, in step S1, the raw materials include Li source Li2S, P source P2S5, Cl source LiCl, Br source LiBr, W and O source WO3.

[0020] Preferably, the molar ratio of Li2S to P2S5, WO3, LiCl, and LiBr is 1:(0.1-0.5):(0.01-0.1):0.4:0.35.

[0021] As an embodiment of the present invention, in step S1, the raw materials are pre-mixed in an inert gas (argon) environment. The ball milling is performed in a sealed ball milling jar fixed on a planetary ball mill.

[0022] As an embodiment of the present invention, in step S1, the rotation speed of the ball mill is 200 rpm-600 rpm, the ball milling time is 5 h-20 h, and the ball to material ratio is 1:(1-30).

[0023] As an embodiment of the present invention, in step S2, the tableting pressure is 120 MPa-600 MPa.

[0024] As an embodiment of the present invention, in step S2, the sintering heating rate is 0.1°C / min-5°C / min, the sintering temperature is 200°C-600°C, and the sintering time is 4h-24h.

[0025] As an embodiment of the present invention, in step S2, vacuum sintering is to place the electrolyte sheet in a quartz tube or a glass tube, vacuum seal it, and place the sealed quartz tube or glass tube in a muffle furnace for sintering.

[0026] As an embodiment of the present invention, in step S2, the sintered electrolyte sheet is ground for a grinding time of 15 min to 60 min.

[0027] In addition, the present invention also provides an air-stable argyrodite-type solid electrolyte for use in an all-solid-state battery.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) To address the problem of low ionic conductivity of sulfide solid electrolytes, the present invention uses ions with large ionic radius for doping modification. The introduction of ions with large ionic radius can increase the unit cell size, broaden the channel for lithium ion transmission, and ultimately improve the ionic conductivity and increase its energy density in the solid electrolyte system.

[0030] (2) To address the problem of poor air stability, the present invention uses O element to replace part of the sulfur element in the sulfide solid electrolyte. Since the PO bond strength is greater than the PS bond, a more stable chemical bond is generated, thereby improving its stability to air and making it possible to carry out large-scale production in air.

[0031] (3) In order to solve the problem of interface stability, the electrolyte of the present invention can inhibit the formation of a space layer between the positive electrode and the electrolyte interface. The improvement of the ionic conductivity of the electrolyte system of the present invention can reduce the possibility of Li ion deposition at the electrode interface, reduce the interface impedance, and improve its electrochemical performance in the solid electrolyte system. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0033] Figure 1 This is a SEM image of the solid electrolyte prepared in Example 1;

[0034] Figure 2 The XRD pattern of the solid electrolyte prepared in Example 1;

[0035] Figure 3 Air stability test of the solid electrolytes obtained in Examples and Comparative Examples;

[0036] Figure 4 Testing of ionic conductivity of solid electrolytes obtained in Examples and Comparative Examples;

[0037] Figure 5 The first cycle charge and discharge performance comparison of the solid electrolyte obtained in the embodiment and the comparative example;

[0038] Figure 6 Solid electrolytes prepared for Example 1 and Comparative Example 2 and Comparative Example 3 were used in all-solid-state batteries for cyclic stability testing (1C);

[0039] Figure 7 The impedance comparison of solid-state batteries assembled with solid electrolytes prepared in Comparative Example 1, Comparative Example 3 and Example 1 after 10 cycles;

[0040] Figure 8 An electrolyte membrane prepared by a solid electrolyte dry method is prepared according to Example 1. DETAILED DESCRIPTION

[0041] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following examples are implemented on the premise of the technical solution of the present invention, provide detailed implementation methods and specific operation processes, and will help those skilled in the art to further understand the present invention. It should be pointed out that the protection scope of the present invention is not limited to the following embodiments, and several adjustments and improvements made under the premise of the concept of the present invention all belong to the protection scope of the present invention.

[0042] The present invention adopts the following steps to test the charge and discharge performance:

[0043] First, NCM811 composite cathode material was prepared: NCM811 and the solid electrolyte prepared in step 2) above and vapor-grown carbon fiber (VGCF) were weighed into a 25 mL zirconia ball mill according to a mass ratio of 16:3:1. The total mass of the material was 1 g, the ball-to-material ratio was controlled to be 20:1, and the diameter of the zirconia ball milling beads used was 5 mm. Then the sealed ball mill was fixed on a high-energy planetary ball mill and ball milled at 400 r / min for 4 hours. Finally, the NCM811 composite cathode material was obtained. Then, Li / In was used as the negative electrode, the prepared solid electrolyte was used as the electrolyte layer, the all-solid-state battery was assembled, and the charge and discharge performance was tested.

[0044] Example 1

[0045] In a glove box filled with argon, Li2S (0.6138g), P2S5 (0.7366g), LiCl (0.227g), LiBr (0.4072g), and WO3 (0.0156g) were pre-mixed at a molar ratio of 1.995: 0.495: 0.8: 0.7: 0.01, and then placed in a sealed ball mill jar and ball milled at a ball-to-material ratio of 30:1. Then, the ball mill was fixed at a planetary ball mill at 500rpm for 7h to obtain the initial solid electrolyte powder. The obtained electrolyte powder was pressed into a sheet at a pressure of 400MPa to obtain an electrolyte sheet, which was then vacuum sealed. The sealed quartz tube or glass tube was placed in a muffle furnace and heated at 0.5℃ / min, calcined at 480℃ for 7h, then naturally cooled to room temperature, and then ground to obtain the final solid electrolyte (Li 5.49 P 0.99 W 0.01 S 4.47 O 0.03 Cl 0.8 Br 0.7 ), the SEM image of the solid electrolyte is shown in Figure 1 As shown, the XRD pattern is Figure 2 shown.

[0046] Performance Test:

[0047] Test of ionic conductivity: Weigh 100 mg of the prepared solid electrolyte (Li 5.49 P 0.99 W 0.01 S 4.47 O 0.03 Cl 0.8 Br 0.7 ) in a 10mm stainless steel tablet pressing mold, press the electrolyte sheet at a pressure of 360MPa, then add 9mm lithium sheets (the thickness of the lithium sheets is 15 microns) on both sides of the electrolyte sheet, and then install Cu current collectors on both sides to complete the packaging. Take out the battery mold, put it in the battery fixture, and press it at a pressure of 50MPa to obtain a sandwich-type all-solid-state battery. Then measure the ionic conductivity of the solid electrolyte σ=13ms / cm.

[0048] Air stability test: The obtained solid electrolyte (Li 5.49 P 0.99 W 0.01 S 4.47 O 0.03 Cl 0.8 Br 0.7 ) was placed in dry air, and then the gas changes over time before and after exposure to air were tested. After 15 minutes, the amount of gas released by the prepared solid electrolyte was 0.36cm 3 / g.

[0049] Pressure battery performance test: Weigh 100 mg of the prepared solid electrolyte (Li 5.49 P 0.99 W 0.01 S 4.47 O 0.03 Cl 0.8 Br 0.7 ) in a 10mm stainless steel tablet pressing mold, press the electrolyte sheet at a pressure of 360MPa, then add 10mg of the composite positive electrode material prepared by the above method on one side of the electrolyte sheet, press it again at a pressure of 150MPa, then demold it and put it into a special battery test mold, then add a 9mm lithium indium sheet on the other side of the electrolyte sheet (the thickness of the lithium indium sheet is 30 and 100 microns respectively), and finally load the Al sheet current collector on the positive electrode side and the Cu current collector on the negative electrode side to complete the packaging. Take out the battery mold, put it in the battery fixture, and press it at a pressure of 50MPa to obtain a sandwich-type all-solid-state battery. The assembled full battery is subjected to a capacitor discharge test. At room temperature and a rate of 0.1C, the first cycle discharge specific capacity can reach 221 mAh / g.

[0050] Example 2

[0051] In a glove box filled with argon, Li2S (0.6166g), P2S5 (0.7444g), LiCl (0.2277g), LiBr (0.4082g), and WO3 (0.00312g) were pre-mixed at a molar ratio of 1.999: 0.499: 0.8: 0.7: 0.002, and then placed in a sealed ball mill jar and ball milled at a ball-to-material ratio of 30:1. Then, the mixture was fixed in a planetary ball mill and ball milled at 500rpm for 7h to obtain a preliminary solid electrolyte powder. The obtained electrolyte powder was pressed into a tablet at a pressure of 400MPa to obtain an electrolyte tablet, which was then vacuum sealed. The sealed quartz tube or glass tube was placed in a muffle furnace and heated at 0.5℃ / min, calcined at 480℃ for 7h, and then naturally cooled to room temperature. The final solid electrolyte (Li 5.498 P 0.998 W 0.002 S 4.494 O 0.006 Cl 0.8 Br 0.7 ).

[0052] Performance Testing:

[0053] Test of ionic conductivity: Weigh 100 mg of the prepared solid electrolyte (Li 5.498 P 0.998 W 0.002 S 4.494O 0.006 Cl 0.8 Br 0.7 ) in a 10mm stainless steel tablet pressing mold, press the electrolyte sheet at a pressure of 360MPa, then add 9mm lithium sheets (the thickness of the lithium sheets is 15 microns) on both sides of the electrolyte sheet, and then install Cu current collectors on both sides to complete the packaging. Take out the battery mold, put it in the battery fixture, and press it at a pressure of 50MPa to obtain a sandwich-type all-solid-state battery. Then measure the ionic conductivity of the solid electrolyte σ=9ms / cm.

[0054] Air stability test: The obtained solid electrolyte (Li 5.498 P 0.998 W 0.002 S 4.494 O 0.006 Cl 0.8 Br 0.7 ) was placed in dry air, and then the gas changes over time before and after exposure to air were tested. After 15 minutes, the amount of gas released by the prepared solid electrolyte was 0.56cm 3 / g.

[0055] Pressure battery performance test: Weigh 100 mg of the prepared solid electrolyte (Li 5.49 P 0.99 W 0.01 S 4.47 O 0.03 Cl 0.8 Br 0.7 ) in a 10mm stainless steel tablet pressing mold, press the electrolyte sheet at a pressure of 360MPa, then add 10mg of the composite positive electrode material prepared by the above method on one side of the electrolyte sheet, press it again at a pressure of 150MPa, then demold it and put it into a special battery test mold, then add a 9mm lithium indium sheet on the other side of the electrolyte sheet (the thickness of the lithium indium sheet is 30 and 100 microns respectively), and finally load the Al sheet current collector on the positive electrode side and the Cu current collector on the negative electrode side to complete the packaging. Take out the battery mold, put it in the battery fixture, and press it at a pressure of 50MPa to obtain a sandwich-type all-solid-state battery. The assembled full battery is subjected to a capacitor discharge test. At room temperature and a rate of 0.1C, the first cycle discharge specific capacity can reach 200 mAh / g.

[0056] Example 3

[0057] In a glove box filled with argon, Li2S (0.5824g), P2S5 (0.65g), LiCl (0.1506g), LiBr (0.2204g), WO3 (0.396g) were pre-mixed at a molar ratio of 1.95: 0.45: 0.8: 0.7: 0.1, and then placed in a sealed ball mill, ball milled at a ball-to-material ratio of 30:1, and then fixed in a planetary ball mill at 500rpm for 7h to obtain the initial solid electrolyte powder. The obtained electrolyte powder was pressed at a pressure of 400MPa to obtain electrolyte sheets, which were then vacuum sealed. The sealed quartz tube or glass tube was placed in a muffle furnace and heated at 0.5℃ / min, calcined at 480℃ for 7h, then cooled naturally to room temperature, and then ground to obtain the final solid electrolyte.

[0058] Performance Test:

[0059] Test of ionic conductivity: Weigh 100 mg of the prepared solid electrolyte (Li 5.4 P 0.9 W 0.1 S 4.2 O 0.3 Cl 0.8 Br 0.7 ) in a 10mm stainless steel tablet pressing mold, press the electrolyte sheet at a pressure of 360MPa, then add 9mm lithium sheets (the thickness of the lithium sheets is 15 microns) on both sides of the electrolyte sheet, and then install Cu current collectors on both sides to complete the packaging. Take out the battery mold, put it in the battery fixture, and press it at a pressure of 50MPa to obtain a sandwich-type all-solid-state battery. Then measure the ionic conductivity of the solid electrolyte σ=8ms / cm.

[0060] Air stability test: The obtained solid electrolyte (Li 5.4 P 0.9 W 0.1 S 4.2 O 0.3 Cl 0.8 Br 0.7 ) was placed in dry air, and then the gas changes over time before and after exposure to air were tested. After 15 minutes, the amount of gas released by the prepared solid electrolyte was 0.80cm 3 / g.

[0061] Pressure battery performance test: Weigh 100 mg of the prepared solid electrolyte (Li 5.49 P 0.99 W 0.01 S 4.47 O 0.03 Cl 0.8 Br 0.7) in a 10mm stainless steel tablet pressing mold, press the electrolyte sheet at a pressure of 360MPa, then add 10mg of the composite positive electrode material prepared by the above method on one side of the electrolyte sheet, press it again at a pressure of 150MPa, then demold it and put it into a special battery test mold, then add a 9mm lithium indium sheet on the other side of the electrolyte sheet (the thickness of the lithium indium sheet is 30 and 100 microns respectively), and finally load the Al sheet current collector on the positive electrode side and the Cu current collector on the negative electrode side to complete the packaging. Take out the battery mold, put it in the battery fixture, and press it at a pressure of 50MPa to obtain a sandwich-type all-solid-state battery. The assembled full battery is subjected to a capacitor discharge test. At room temperature and a rate of 0.1C, the first-cycle discharge specific capacity can reach 180mAh / g.

[0062] Comparative Example 1

[0063] The difference between this comparative example and Example 1 is that the raw materials Li2S, P2S5, LiCl, LiBr, and WO3 are replaced by Li2S, P2S5, and LiCl in a molar ratio of 2:0.5:1.5 to prepare undoped Li 5.5 PS 4.5 Cl 1.5 Electrolyte. The ionic conductivity of the solid electrolyte is then measured at σ = 6ms / cm.

[0064] Comparative Example 2

[0065] The difference between this comparative example and Example 1 is that the W element is not doped, and the raw materials are Li2S, P2O5, LiCl, and LiBr. The molar ratio is 4.47:0.006:0.8:0.7, which is used to prepare Li2S without W doping. 10.44 P 0.012 S 4.47 O 0.03 Cl 0.8 Br 0.7 Electrolyte. The test steps and methods are the same as those in Example 1. Then the ionic conductivity σ=5ms / cm of the solid electrolyte is measured.

[0066] Comparative Example 3

[0067] The difference between this comparative example and Example 1 is that the O element is not doped, and the raw materials are Li2S, P2S5, LiCl, LiBr, and WS3. The molar ratio is 2.025:0.495:0.8:0.7:0.01, which is used to prepare Li2S without O doping. 5.55 P 0.99 W 0.01 S 4.53 Cl 0.8 Br 0.7 Electrolyte. The test steps and methods are the same as those in Example 1. Then the ionic conductivity σ=3ms / cm of the solid electrolyte is measured.

[0068] The present invention mainly introduces multiple elements (W, O, Br) into the argyrodite solid electrolyte at the same time, wherein the metal element W with a large ion radius replaces part of the P position, which can expand the unit cell size, thereby being more conducive to Li + Transport in the structure. Br replaces some Cl element positions to increase the disorder of Br and Cl in the electrolyte system, thereby reducing its activation energy and improving ionic conductivity. O replacing S will increase the binding energy of MP4 tetrahedron, thereby improving the air stability of sulfide electrolytes. As a result, the prepared solid electrolyte has high ionic conductivity, air stability and electrochemical stability at the same time, fundamentally addressing the various challenges faced in the development of all-solid-state batteries, and providing solutions for all-solid-state battery systems that pursue high energy density, high safety and long cycle life.

[0069] The discharge specific capacity and coulombic efficiency of each embodiment of the present invention and the comparative example in the first cycle are shown in Table 1 below:

[0070] Table 1

[0071]

[0072] The air stability test of the solid electrolyte obtained in the embodiment and the comparative example is as follows Figure 3 As shown;

[0073] The ionic conductivity of the solid electrolyte obtained in the embodiments and comparative examples is tested as follows: Figure 4 As shown;

[0074] Comparison of the first cycle charge and discharge performance of the solid electrolyte obtained in the embodiment and the comparative example Figure 5 As shown;

[0075] The solid electrolyte prepared in Example 1 and Comparative Example 2 was used in the all-solid-state battery for the cycle stability test (1C). Figure 6 As shown;

[0076] Comparison of impedance after 10 cycles of solid electrolyte assembled solid-state batteries prepared in Example 1 and Comparative Example 1 and Comparative Example 3 Figure 7 As shown;

[0077] Figure 8 The electrolyte membrane prepared by the solid electrolyte dry method in Example 1 is as follows Figure 8 Attached Figure 8 The film-forming property test of the modified solid electrolyte of the present invention is given (film-forming is possible), while the comparative test shows that the undoped or singly doped W or O element cannot form a film, so only when W and O are doped at the same time can the film-forming property of the solid electrolyte be improved.

[0078] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A argyrodite-type solid electrolyte, characterized in that: The general chemical formula is Li 5.5-x P 1-x W x S 4.5- 3x O 3x Cl y Br 1.5-y ; Among them, the value of x is 0.001<x<0.01, 0.7<y<0.

9.

2. A method for preparing the argyrodite-type solid electrolyte according to claim 1, characterized in that: The steps include: S1. Premixing the raw materials according to the molar ratio and ball milling to obtain solid electrolyte powder; S2. Pressing the solid electrolyte powder into sheets to obtain electrolyte sheets, and vacuum sintering to obtain argyrodite-type solid electrolyte.

3. The preparation method according to claim 2, characterized in that: In step S1, the raw materials include Li source Li2S, P source P2S5, Cl source LiCl, Br source LiBr, W and O source WO3.

4. The preparation method according to claim 2, characterized in that: In step S1, the raw materials are pre-mixed in an inert gas environment; the ball milling is performed by placing the raw materials in a sealed ball milling jar and fixing them in a planetary ball mill.

5. The preparation method according to claim 2, characterized in that: In step S1, the ball milling speed is 200 rpm-600 rpm, the ball milling time is 5 h-20 h, and the ball-to-material ratio is 1:(1-30).

6. The preparation method according to claim 2, characterized in that: In step S2, the tableting pressure is 120MPa-600MPa.

7. The preparation method according to claim 2, characterized in that: In step S2, the sintering temperature is 200°C-600°C, and the sintering time is 4h-24h; And / or, the heating rate of sintering is 0.1°C / min-5°C / min.

8. The preparation method according to claim 2, characterized in that: In step S2, the sintering is performed by placing the electrolyte sheet in a quartz tube or a glass tube, vacuum sealing it, and placing the sealed quartz tube or glass tube in a muffle furnace for sintering.

9. The preparation method according to claim 2, characterized in that: In step S2, the sintered electrolyte sheet is ground for a time of 15 min to 60 min.

10. Use of the argyrodite-type solid electrolyte as claimed in claim 1 in an all-solid-state battery.

Citation Information

Patent Citations

  • Doped phosphorus-sulfur iodide solid electrolyte and preparation method and application thereof

    CN111092262A